Relationship between disorders of adipose tissue hormones and interleukins in patients with hypertension and comorbid pathology - B. O. Shelest (Zaporožskij Medicinskij Žurnal)
The purpose of research – was to improve the efficiency of diagnostics of arterial hypertension (AH) with comorbid disorders (diabetes mellitus (DM) and obesity) by studying hormones of adipose tissue (leptin and adiponectin) and the inflammatory markers – interleukin 6 and 10.